2019
DOI: 10.3390/plants8120611
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Drought Stress on Antioxidant Responses and Accumulation of Flavonolignans in Milk Thistle (Silybum marianum (L.) Gaertn)

Abstract: Biosynthesis and accumulation of flavonolignans in plants are influenced by different environmental conditions. Biosynthesis and accumulation of silymarin in milk thistle (Silybum marianum L.) were studied under drought stress with respect to the antioxidant defense system at the physiological and gene expression level. The results revealed a reduction in leaf chlorophyll, ascorbic acid, and glutathione contents. In contrast, H2O2, proline, and antioxidative enzyme activities, such as superoxide dismutase (SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 82 publications
3
22
0
Order By: Relevance
“…The results were in agreement with a previous report by Oh et al, which showed that the drought stress induced by withholding water for 4 days improved the TPC and TAC in lettuce [15]. Furthermore, numerous studies have shown that drought stress enhances one or both enzymatic and nonenzymatic antioxidants in a wide range of plants [31][32][33][34][35]. Moderate drought stress can improve plant drought tolerance, and enhance the antioxidant system [30,36].…”
Section: Bioactive Compounds Antioxidant Activity and Plant Growth supporting
confidence: 92%
“…The results were in agreement with a previous report by Oh et al, which showed that the drought stress induced by withholding water for 4 days improved the TPC and TAC in lettuce [15]. Furthermore, numerous studies have shown that drought stress enhances one or both enzymatic and nonenzymatic antioxidants in a wide range of plants [31][32][33][34][35]. Moderate drought stress can improve plant drought tolerance, and enhance the antioxidant system [30,36].…”
Section: Bioactive Compounds Antioxidant Activity and Plant Growth supporting
confidence: 92%
“…Plants alleviate stress-induced oxidative damage by changing antioxidant enzymes activity and accumulation of non-enzyme antioxidants, such as ascorbic acid, flavonoids, etc. (Wang et al 2018;ElSayed et al 2019). In milk thistle (Silybum marianum [L.] Gaertn), the activities of antioxidative enzymes, such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), and peroxidase (POD), increased under drought stress, and the biosynthesis and accumulation of flavonolignans (non-enzyme antioxidants) also increased during drought stress (ElSayed et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Wang et al 2018;ElSayed et al 2019). In milk thistle (Silybum marianum [L.] Gaertn), the activities of antioxidative enzymes, such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), and peroxidase (POD), increased under drought stress, and the biosynthesis and accumulation of flavonolignans (non-enzyme antioxidants) also increased during drought stress (ElSayed et al 2019). Flavonoids are secondary metabolites in the phenylpropane pathway and reportedly, they play important roles in plant responses to biological and non-biological stresses (Liu et al 2011a;Akram et al 2018;Brunetti et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The standardized extract obtained from the dried fruits of S. marianum contains 70–80% of silymarin and 20–30% of polymeric and oxidized polyphenolic compounds [ 3 ]. Silymarin is a flavonolignan complex of polyphenolic molecules, which includes diasterereoisomers silybin A and silybin B (whose mixture in a 1:1 ratio is named silibinin), silydianin, silychristin, isosilychristin, isosilybin A and isosilybin B, and the taxifolin flavanonol [ 4 ]. Biosynthesis of silybins from taxifolin and coniferyl alcohol is schematized in Figure S1 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%